Public Procurement Price Variance in Kenya: Extent, Drivers, and Proposed Mitigation - Kamoni, Peter (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
Developing economies, often dependent on donor funding and debt, such as Kenya could benefit from sealing budget leakages. Public procurement price variance is deemed a key inefficiency in public expenditure contributing to the loss of colossal amounts of Money. Mechanisms to achieve realistic public procurement prices are stipulated in the existing public procurement regulatory regime; However, Price variances, manifesting in inflated tenders, are abound. The extent and drivers are yet to be empirically examined. This study adopted an exploratory approach to examine the extent of public procurement price variance; by conducting variance analysis of market prices and prices of goods contained in procurement contracts of 336 public procuring entities (Ministries, Departments, and Agencies) in Kenya in the 2022/2023 Financial Year. Analysis of data drawn from a random sample of 40 MDAs, indicates that all items acquired by MDAs were overpriced: at between 20% and 220% of the market price. Analysis of drivers of overpricing ranked: “budgeted kickbacks/bribes”; “Response to Late Payments by MDAs”; “Collusive Bidding”; and “Over-use of non-competitive methods”; as key drivers. The study reviewed the price oversight mechanism of the public procurement system in Kenya and recommends the adoption of a live internal public procurement audit model to monitor and oversight pricing. This will require a review of the regulatory regime to entrench the internal procurement audit model into the public procurement process. The study also recommends a public procurement study to examine the extent and magnitude of procurement price variance across Kenya and its fiscal effect on the Economy.